In sickness and in health—A scoping review on social virtual reality clinical applications - Stephanie P Belina; Sara J Czaja; JoAnn Difede; Kevin J Pain; M Carrington Reid; Andrea Stevenson Won (Digital Health)
Objective Evidence of virtual reality's (VR) efficacy in hospital settings coupled with the rise of inexpensive consumer devices have led to the development of social virtual reality (SVR) applications being incorporated in hospital settings. SVR provides opportunities for social interactions in virtual environments, allowing individuals to virtually socialize, regardless of geographic or mobility constraints. However, the full range of potential applications and the challenges of deploying SVR in hospital settings remain unexplored. We conducted a scoping review to characterize SVR applications studied in hospital settings to better understand SVR use for inpatient populations overall and in preparation for a National Institutes of Health (NIH)-funded project investigating SVR use with a specific clinical population. Methods In this scoping review, we searched MEDLINE, Embase, Scopus, APA PsycInfo, CINAHL, IEEE, and ACM Digital Library. After screening 2334 studies and reviewing 146 full texts, we identified 12 studies as eligible for analysis. Eleven of the 12 were published in the past 7 years, with none older than 12 years. Results As this is an emerging field, many publications were case or pilot studies, with small sample sizes ranging from 3 to 200 participants, and with mean participant ages that ranged from 9 to 75 years. Patient populations included those with stroke, cancer, COVID, as well as other health conditions. Conclusion Discussion of privacy and accessibility concerns was limited, as was the reported influence of SVR on measures associated with inpatient medical treatment (such as, adherence to clinical treatment while in the hospital while in a SVR intervention), which we highlight as critical issues for SVR's clinical use. We discuss our findings in the context of potential future directions for research in this area.